The Level of School Health Environment in the General Directorate of Education in Taif Governorate from the Perspective of Health Supervisors and Its Relationship with Some Variables - Al-Salmi, Sulaiman Hamoud (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the level of the school health environment in the General Administration of Education in Taif Governorate from the perspective of male and female health supervisors, and to examine the effect of the variables (sector, educational stage, and educational office) on their views. The researcher adopted the descriptive survey method, using a questionnaire distributed to a sample of 101 health supervisors in internal education offices: 40 boys’ schools and 61 girls’ schools. The results revealed that the overall level of the school health environment was moderate, with a mean score of (2.93) and a percentage of (77.97%). Statistically significant differences were found between boys’ and girls’ schools in favor of girls’ schools. There were also significant differences across educational stages (elementary, intermediate, secondary, and educational complexes) in favor of the secondary level. However, no statistically significant differences were found based on the educational office variable. Key recommendations included enhancing the level of the school health environment through continuous monitoring by the relevant educational authorities, organizing training courses and applied workshops to train health supervisors on how to inspect and maintain the school environment, and conducting a similar study from the perspective of school principals.